Gravito-electromagnetic fields and superconductors in a regime of weak static gravitational field. (1st May 2023) - Das, D K; Panda, S; Das, Salila
Abstract: A Deeper interweaving of different scientific areas has always proven to be a powerful tool for improving our understanding of several fascinating physical aspects of the world. For example, researchers worldwide have investigated the intriguing existence of the interaction between gravity and superconductivity in recent decades, owing to its enormous conceptual implications and various potential applications. Different theories using various approaches and techniques have been proposed to predict these interactions. To study the anomalous couplings between the super condensate and local gravitational field, we provide a detailed calculation of the thermodynamic properties and coherence length on behalf of the gravitational wave vector. In addition, this study provides a framework for calculating the gravitational penetration depth compared with the electromagnetic (E.M.) penetration depth. Furthermore, we demonstrate macroscopic quantum interference events by applying the Josephson effect using a superconducting quantum interface device (SQUID) link. Finally, similar to other calculations, we demonstrate how the quantum of the gravity flux is used to manage a sinusoidally oscillating current. This phenomenon will help future researchers study the effects of gravitational perturbation on supercurrents and super-condensates, and the latter could be used as 'gravitational antennas' for gravitational wave detection.